2018
DOI: 10.1177/1934578x1801300612
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoids from Desmodium heterophyllum Aerial Parts

Abstract: Five isoflavanoids including one new, (3R)-2',4',5,7-tetrahydroxy-6-methylisoflavanone (1), were isolated from the aerial parts of Desmodium heterophyllum. Their structures were elucidated using spectroscopic methods. Their inhibitory effects on digestive enzymes α-glucosidase and α-amylase were evaluated. Genistein (5) and dalbergioidin (2) inhibited both enzymes. Their IC 50 values were found at 110.4 and 162.8 µM for α-amylase, and at 257.3 and 412.6 µM for α-glucosidase, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The inconsistency of the inhibitory mechanism could result from the difference in the α-glucosidase type used in these studies. Additionally, this isoflavonoid was also reported to be more potent than acarbose in the α-amylase inhibition assay in two references [ 130 , 233 ]. On the other hand, the inhibitory potency of formononetin ( 167 ) towards α-glucosidase, is still controversial, with two out of three studies reporting it to be more effective than acarbose with micromolar potency [ 130 , 235 ] while the result from Jia et al showed a reverse pattern [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistency of the inhibitory mechanism could result from the difference in the α-glucosidase type used in these studies. Additionally, this isoflavonoid was also reported to be more potent than acarbose in the α-amylase inhibition assay in two references [ 130 , 233 ]. On the other hand, the inhibitory potency of formononetin ( 167 ) towards α-glucosidase, is still controversial, with two out of three studies reporting it to be more effective than acarbose with micromolar potency [ 130 , 235 ] while the result from Jia et al showed a reverse pattern [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Ha et al (2018), dalbergioidin ( 168 ) was extracted from Desmodium heterophyllum aerial parts and evaluated for its anti-diabetic properties [ 233 ]. According to the results, this substance was found to exhibit stronger inhibition against α-glucosidase but weaker inhibition against α-amylase, in comparison with acarbose in the same experimental conditions [ 233 ]. Puerarin ( 169 ) is the only isoflavonoid glycoside included in our current review.…”
Section: Resultsmentioning
confidence: 99%
“…Peonidin 3-O-glucoside was detected in TN50E, TNW70M and TNW80M conditions and has been previously described to be as efficient (IC 50 = 192.3 μg/mL) as acarbose (IC 50 = 180.2 μg/mL) in inhibiting rat intestinal α-glucosidase [ 73 ]. Dalbergioidin, an isoflavanone that was abundant in TNW70M and TNW80M fractions has been found to efficiently inhibit α-glucosidase (IC 50 = 412.6 μM) compared to acarbose (IC 50 = 671.4 μM) [ 74 ]. The xanthone garbogiol has also been found to exhibit considerable α-glucosidase inhibition (IC 50 = 21.2 μM) compared to acarbose (IC 50 = 214.5 μM) [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…D. gangeticum has been used for the treatment of asthma, stomatitis, arthritis, eczema, or some other diseases [1]. Previous studies proved the contents of flavonoids, alkaloids, and sterols in D. gangeticum with hepatoprotective, antiinflammatory, antileishmanial, immunomodulatory, cardioprotective, antinociceptive wound healing, antidiabetic, and antiulcer activities [3][4][5][6]. Nitric oxide (NO) has been known to involve in the regulation of various physiological processes in mammals and the overproduction of NO is responsible for the pathological development of inflammation, cancer, and diabetes [7,8].…”
Section: Introductionmentioning
confidence: 99%